Pelatihan Pembuatan Desain, Lambang Dan Ikon Olahraga: Pengembangan Kewirausahaan Konveksi Pakaian Di Masa Pandemi Covid 19 - Iis Marwan; Hari Waluyo Sedjati; Akhmad Satori; Hendra Gunawan Gunawan (Pusat Kajian Pendidikan Olahraga, Kesehatan dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Uiveristas Negeri Padang Jl. Prof. Hamka, Air Tawar Padang 25131 Telp. 0751-7059901, 2022)
The sports industry is one of the most important aspects in the economic development of a country. Sports can be used as a business in various kinds of businesses, one of which is a provider of sports clothing. Every sporting event the need for designs, types, models, as well as logos and uniforms is very diverse. A large industry with high personal abilities supported by modern equipment and current information does not cause many problems in terms of making designs, logos and icons desired by users, including marketing. However, small-scale sports convection entrepreneurs face various obstacles and obstacles, especially in terms of production, processing, marketing, human resources, design and technology, capital, as well as the business climate with the COVID-19 pandemic situation. To overcome partner problems, counseling and assistance are needed. as well as training on designing, logos and icons for sports activities as well as providing information on sports schedules locally, regionally, nationally and internationally. The purpose of implementing community service is partners are able to create designs, logos, and sports icons, as well as understand sports activities that require uniforms or sports souvenirs. Community Service Methods carry out training, counseling and mentoring for partner members (convection entrepreneurs and employees, 34 sports shop/distribution owners plus administrators of the Association of Residents and Neighbors Association (ARWT), sports branches and administrators of the Indonesian National Sports Committee (KONI) Tasikmalaya City as many as 38 people. Implementation time from June to August 2021. Conducted offline and online. Instruments of success are interviews, observations of production results and community responses to product users. The results obtained are 92% satisfied with the implementation model; 86% Small and Medium Enterprises (SMEs) succeeded in carrying out the manufacture of production, and 64% there was an increase in people's purchasing power of production